2002
DOI: 10.1124/jpet.102.037010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adenosine A1Receptor in Angiotensin II- and Norepinephrine-Induced Renal Vasoconstriction

Abstract: We investigated the contributions of adenosine A 1 receptors to angiotensin II-and norepinephrine-induced renal vasoconstriction. Intrarenal administrations of angiotensin II (3, 10, and 30 ng) or norepinephrine (100 and 500 ng) produced dose-dependent renal vasoconstriction in anesthetized dogs. Under resting conditions, angiotensin II (30 ng) and norepinephrine (500 ng) significantly decreased renal blood flow by Ϫ43 Ϯ 3 and Ϫ19 Ϯ 2%, respectively (n ϭ 21). Intra-arterial infusion of adenosine (5 g/kg/min) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 30 publications
1
23
2
Order By: Relevance
“…Studies from our laboratory have shown that the constrictor effect of ANG II in isolated rabbit afferent arterioles was blocked by ϳ50% when the A1AR inhibitor DPCPX was present in the bath (17), a finding that was reproduced in the present studies in mouse afferent arterioles. In confirmation of an earlier observation, a recent study in dogs showed that the reduction in RBF caused by ANG II was augmented by intrarenal infusion of adenosine and attenuated by the A1AR antagonist KW-3902 (1,6). The present study is the first to demonstrate that the vasoconstricting effects of acute changes in plasma ANG II levels are attenuated in animals with a life-long absence of A1AR.…”
Section: Discussionsupporting
confidence: 74%
“…Studies from our laboratory have shown that the constrictor effect of ANG II in isolated rabbit afferent arterioles was blocked by ϳ50% when the A1AR inhibitor DPCPX was present in the bath (17), a finding that was reproduced in the present studies in mouse afferent arterioles. In confirmation of an earlier observation, a recent study in dogs showed that the reduction in RBF caused by ANG II was augmented by intrarenal infusion of adenosine and attenuated by the A1AR antagonist KW-3902 (1,6). The present study is the first to demonstrate that the vasoconstricting effects of acute changes in plasma ANG II levels are attenuated in animals with a life-long absence of A1AR.…”
Section: Discussionsupporting
confidence: 74%
“…Adenosine and ATP on RBF Measurements of total RBF in the whole kidney have demonstrated an effect of exogenously administered adenosine on RBF characterized by an initial transient renal vasoconstriction that wanes and becomes supplanted by a gradual vasodilation (20,66,67). Churchill and Bidani (68) observed that intravenous infusion of an adenosine A1 receptor agonist, N 6 -cyclohexyl adenosine, decreased renal plasma flow in anesthetized rats.…”
Section: Effects Of Exogenously Administeredmentioning
confidence: 99%
“…However, this hypothesis has remained controversial because systemic administration of adenosine antagonists does not block RBF or glomerular filtration rate (GFR) autoregulation (94,95). Furthermore, although the TGF mediator must exert selective actions on preglomerular arterioles (20,21), several studies have demonstrated that adenosine or adenosine A1 receptor agonists elicit significant vasoconstriction of efferent arterioles (13,18) and vasa recta (96). It is also recognized that TGF-mediated changes in afferent arteriolar resistance are sustained for long periods (21,22).…”
Section: Possible Roles Of Adenosine and Atp In The Tubuloglomerular mentioning
confidence: 99%
See 2 more Smart Citations